2022
DOI: 10.14309/ajg.0000000000001937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Antibiotics in Patients Admitted to Hospital With Decompensated Cirrhosis: Lessons From the ATTIRE Trial

Abstract: Hospital-acquired infections (HAI) are common in cirrhosis with antibiotics frequently used to prevent infections, but their efficacy for this role is unknown. To investigate this, we used Albumin to Prevent Infection in Chronic Liver Failure (ATTIRE) data to evaluate whether antibiotic use in patients without infection prevented HAI. METHODS:In ATTIRE patients without infection at baseline grouped by antibiotic prescription or not, we studied HAI during trial treatment period and mortality, with propensity sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The current clinical trial by Louvet et al suggests no role for prophylactic prescription of antibiotics when treating all patients who have alcohol-related hepatitis with corticosteroids . This finding was similar to observations from a post hoc analysis of hospitalized patients with decompensated cirrhosis in the ATTIRE clinical trial, many of whom had alcohol-related liver disease . In this study, prescription of antibiotics in 777 patients hospitalized with decompensated cirrhosis without documented infection did not improve survival compared with those who did not receive antibiotics .…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The current clinical trial by Louvet et al suggests no role for prophylactic prescription of antibiotics when treating all patients who have alcohol-related hepatitis with corticosteroids . This finding was similar to observations from a post hoc analysis of hospitalized patients with decompensated cirrhosis in the ATTIRE clinical trial, many of whom had alcohol-related liver disease . In this study, prescription of antibiotics in 777 patients hospitalized with decompensated cirrhosis without documented infection did not improve survival compared with those who did not receive antibiotics .…”
supporting
confidence: 86%
“…This finding was similar to observations from a post hoc analysis of hospitalized patients with decompensated cirrhosis in the ATTIRE clinical trial, many of whom had alcohol-related liver disease . In this study, prescription of antibiotics in 777 patients hospitalized with decompensated cirrhosis without documented infection did not improve survival compared with those who did not receive antibiotics . For patients with alcohol-related hepatitis, developing infection while taking corticosteroids is an indicator of poor prognosis and should be treated .…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This emphasises the need to reduce unnecessary antibiotic prescriptions to prevent these life-saving drugs becoming ineffective. Further analyses of the ATTIRE patients not considered by their clinicians to have an infection revealed no differences in subsequent HAI comparing antibiotic treated to nonantibiotic treated (approximately 20% for both) ( 4 , 5 ). Twenty-eight-day mortality was significantly higher in antibiotic-treated patients, likely reflecting their increased disease severity and when we matched groups using propensity scoring, there were no differences in HAI or mortality.…”
mentioning
confidence: 95%
“…Given the high incidence and severe impact of bacterial infections in patients with cirrhosis, it is likely that antibiotics are overused in this population. In fact, a recent sub-analysis of the ATTIRE clinical trial suggested that half of the antibiotics prescribed to hospitalized patients with decompensated cirrhosis might not be necessary[ 43 ].…”
Section: Introductionmentioning
confidence: 99%